Superselective methohexital challenge prior to intracranial endovascular embolization. (May 2019) - Bican, Orhan; Cho, Charles; Suarez-Roman, Areli; Nguyen, Viet; Lee, Leslie; Le, Scheherazade; Heit, Jeremy; Dodd, Robert; López, Jaime
Highlights: Pharmacologic PT can be performed under general anesthesia (GA) using IONM modalities. Specificity of PT was 100% in both awake and under general anesthesia groups. PT under GA can be performed with a high specificity comparable to awake testing. Abstract: Pharmacologic provocative testing (PT) and intraoperative neurophysiologic monitoring (IONM) both mitigate and predict risks associated with endovascular embolization procedures. We present a series of patients undergoing endovascular intracranial embolization predominantly for AVMs both under general anesthesia and awake with the use of IONM. We reviewed our database to identify all patients undergoing endovascular procedures between January 1, 2014 and January 1, 2016. Awake patients were tested with SSEP, EEG and real time neurologic examination while TcMEPs were performed in all anesthetized patients. BAEPs were performed in anesthetized patients if indicated. Methohexital was administered as an injection at a dose of 5 mg or 10 mg and repeat testing was performed if needed. Sixty-three endovascular procedures that met criteria were performed in 32 patients. 54 procedures in 28 patients were performed under general anesthesia, 9 procedures in 4 patients were performed in wakefulness. PT was negative in 61 procedures and subsequently completed embolizations without neurological sequelae. In two cases, the testing was positive and the procedure was terminated without embolization in one patient. The other patient underwent embolization at an alternative site without repeat PT. There were no new postoperative neurologic deficits after any of these procedures. Specificity of PT was 100% as none of the patients with a negative provocative test developed a new postoperative neurologic deficit after embolization. To our knowledge, this is the first review of PT with the use of neurophysiologic IONM techniques under general anesthesia. These data suggest a high specificity comparable to awake testing.